PSXIV-25 Peripartum supplementation of vitamins A, D, and E increases monocyte CD14, neutrophil CD11b and lymphocyte CD62L in newborn beef calves. (7th December 2018) - Blakely, L; Kweh, M; Pozadas, M; Canal, L; Maciel, J; Sanford, C; Fontes, P; Oosthuizen, N; DiLorenzo, N; Lamb, G; Nelson, C
Abstract: The objective was to determine the effect of supplemental sources of vitamins A, D, and E fed to cows at peripartum on immune status of calves. Fifty six crossbred beef cows housed at the North Florida Research and Education Center were stratified by age and randomly assigned to 1 of 3 treatments: CTRL (n = 19): mineral supplement containing 9.5 mg (28, 000 IU) of retinyl-acetate and 0.23 mg (9, 200 IU) of vitamin D3 daily; VIT1 (n = 19): supplement with additional 34 mg (100, 000 IU) of retinyl-acetate, 1 mg (40, 000 IU) vitamin D3, and 500 mg (500 IU) a-tocopherol-acetate; or VIT2 (n = 18): supplement with additional 250 mg b-carotene, 1 mg 25-hydroxyvitamin D3, and 1, 000 mg a-tocopherol-acetate. Cows were fed bermudagrass hay ad libitum and treatments were provided individually from 250 d of gestation to 60 d postpartum mixed with cottonseed meal. Blood was sampled from cows and calves at 1, 7, and 30 d after calving for serum IgG1 and peripheral blood leukocyte CD11b, CD14 and CD62L expression. Data were analyzed for the fixed effects of treatment, day, and treatment × day interactions. Concentrations of IgG1 in calf serum were decreased ( P < 0.01) by VIT1 and VIT2 compared to CTRL, while concentrations of IgG1 in colostrum were decreased ( P < 0.05) in VIT1 compared to CTRL, but not in VIT2. A treatment × day interaction ( P < 0.05) indicated that monocyte CD14 expression as well as neutrophil CD11b and T cell CD62L was greater for VIT1 and VIT2 calves vs. CTRL at d 7 but not d 30; however, monocyte CD62L decreased ( P < 0.05) in VIT2 compared with CTRL at d 7 but not d 30. In conclusion, peripartum supplementation of beef cows with vitamins A, D, and E alters cellular and humoral immunity of calves.